A novel, simple near-infrared thoracoscopic technique by a particular route for locating lung nodules - Li, Zhengjun; Xia, Mozhu; Liu, Chang; Xie, Liwei; Wang, Tao; Ren, Yi (Frontiers in Oncology, 2023)
Background：The localization of pulmonary nodules prior to thoracoscopic surgery remains challenging for thoracic surgeons, especially for those nodules that are not visible or palpable on the lung surface.Our study is a simple and effective minimally invasive method using indocyanine green through a special pathway to locate pulmonary nodules and fluorescence thoracoscopic surgery.Methods:Thoracoscopic surgery was performed for 18 undiagnosed peripheral non-solid nodules no larger than 2cm after location.After 0.3mg/kg indocyanine green was injected through peripheral vein, the puncture needle was pulled out after it reached about 1cm in the pulmonary parenchyma near the nodules,Transfer to the operating room.The nodule initially was localized by using a near-infrared thoracoscope to visualize indocyanine green fluorescence.Then thoracoscopic resection was performed.Results:Eighteen patients received this special and simple localization method,underwent near-infrared, image-guided, video-assisted thoracoscopic surgery resection.Median computed tomography (CT) tumor size was 1.2 centimeters.Median depth from the pleural surface is 1.6cm(range, 0.1-4.6cm).The median time of CT-guided intervention was 12min,The duration of thoracoscopic surgery was 67 minutes.Indocyanine green fluorescence was clearly identifified in 17 of 18 patients (94.4%).The surgical margins were all negative on fifinal pathology. The final diagnoses included 17 primary lung cancers, and 1 benign lung tumor.Conclusions:CT guided single puncture of indocyanine green after peripheral intravenous injection is a simple, effective and safe method to locate the nodule.These offer surgeons the ease of localization through direct indocyanine green fluorescence imaging，